Monitoring biodiversity for the EU Marine Strategy Framework Directive: Lessons learnt from evaluating the official reports. (June 2021) - Palialexis, Andreas; Kousteni, Vasiliki; Boicenco, Laura; Enserink, Lisette; Pagou, Kalliopi; Zweifel, Ulla Li; Somma, Francesca; Cheilari, Anna; Connor, David
Abstract: Evaluating environmental policies creates opportunities for harmonising and refining their implementation using a heuristic approach, and considering the knowledge gaps in understanding the complex environmental processes. The European Union's (EU) Marine Strategy Framework Directive (MSFD) is an ambitious legislation that brings together state, pressure, and impact Descriptors of the marine environment, and is built on an ecosystem-based approach to management. Ultimately, the Directive aims to achieve Good Environmental Status (GES) and sustainable use of marine resources. The EU Member States' (MS) reporting obligations for biodiversity monitoring were evaluated, to produce the first EU-wide overview of how monitoring programmes across EU waters are organised. Marine biodiversity monitoring is essential for the management of anthropogenic activities that affect the state of marine ecosystems, to support the understanding of complex marine systems, to determine GES, and to evaluate the effectiveness of the established measures. The EU MS put great effort into adapting their established biodiversity monitoring activities for the existing policy requirements, and to plan new monitoring programmes from the emerging needs of this ambitious policy. The monitoring reports provide a unique source of information, and this evaluation could lead to improve MS' reporting, and harmonise implementation of the policy. Moreover, the evaluation provides a basis for sharing good practices, innovative monitoring standards, and developing joint monitoring programmes that could greatly facilitate the establishment of cost-efficient and accurate monitoring. As such, the recommendations from this policy evaluation could be relevant to any environmental management framework worldwide. Highlights: Regional differences and similarities in marine biodiversity monitoring. Inconsistency in the reporting jeopardised an EU-wide monitoring outline. EU Member States put great effort to report biodiversity monitoring programmes. Majority of EU biodiversity monitoring programmes established for or adapted to MSFD. Different monitoring programmes duration jeopardises harmonisation of GES assessment.